Oficinas expressivas com gestantes usuárias de crack: uma tecnologia social para construção do cuidado - Sales, Laís Maria Germano Canuto (2024)
The use of crack cocaine by women has been associated with an increased prevalence of unplanned pregnancies, sexually transmitted infections (STIs), and human immunodeficiency virus (HIV). This group of women has lower adherence to prenatal consultations and a higher number of gestational complications. The literature and professional experience show that pregnancy-puerperal care services have not adapted to this type of challenge, which causes short- and long-term harm to the care provided to them and their children. Despite the existence of a specific local public policy for this demand, it is clear that care plans are generally not put into practice due to the difficulty in building bonds between pregnant women and health professionals. This study aimed to describe/identify/discuss the meanings that pregnant women attribute to motherhood and the health care received during this period in health services and, from this, to systematize theoretically and methodologically the social technology: “Expressive Workshops with Pregnant Women Who Use Crack”. A qualitative, exploratory social health survey was conducted. To collect data from pregnant women, a sociodemographic questionnaire was applied and a focus group and two expressive offices were held. The data obtained were interpreted using the Thematic Content Analysis technique. Based on the data obtained from the field research and the outline of the theoretical framework, the theoretical and methodological systematization of the social technology was carried out: “Expressive workshops with pregnant women who use crack: a strategy for harm reduction, bond building and care”. It was identified that among the participants there are different conceptions of motherhood, influenced by their life stories, pattern of use, social vulnerabilities, family support or lack thereof. Regarding health care, there were resistance to health services where they feel judged, pressured and without freedom of choice due to normative, moralizing and stigmatizing attitudes on the part of health professionals; adherence to spaces where they feel welcomed, have their rights guaranteed, the opportunity to create bonds and the possibility of learning something. There is a need for health care strategies based on the possibility of building bonds and encouraging the autonomy of these women and the need for constant reflection by professionals regarding which discourses guide their strategies. It is concluded that, in this context, expressive offices have the potential to raise and bring to the debate the anxieties and needs of pregnant women regarding the care they would like to receive, to be a space for reflection by health professionals who would be in contact with other possibilities of coexistence with these women, and thus, it would be a democratic space for building bonds and health care.